Student Engagement and Blended Learning: What’s the connection? Compromiso de los estudiantes y aprendizaje combinado: ¿Cuál es la conexión? - Vaughan, Norman (Educación Superior, 2020)
This article investigates the connection between student engagement and blended learning through the lens of community of inquiry framework (Garrison, 2017). An introduction to student engagement and blended learning are provided followed by an overview to the community of inquiry model. From this framework, seven principles have been derived to design, facilitate, and direct a blended learning approach to teaching and learning.